About the national work of Saint Sava - Bodrožić Đuro (Srpska Politička Misao)
There is no doubt that, when it comes to the spiritual rooting of Serbs, and therefore the estabilishment of a national identity, the key place belongs to Saint Sava. He is the main constant, the spiritual vertical, the central figure in the histiry of the Serbian Orthodox Church and the Serbian people. Of all church dignitaries and saints, the cult of Saint Sava always occupied a central place. He is the creator of the Serbian Orthodox Church and the first Serbian archbishop. His role in the creation of the Serbian church, state and nation made him a fundamental figure in Serbian nationa history. Sain Sava began his historic mission by going to Mount Athos. He knew how important it was that his father Stefan Nemanja, the creatoir of the Serbian state from which the Serbs count their historical time, would join him there. And so it was, Nemanja stepped down from power, became a monk and followed in his son's aootsteps to Mount Athos. Together they built the Serbian monastery on Mount Athos - Hilandar, which would become a source of Serbian literacy, education and culture. Sava compiled a biography of his father, a work that is considered the beginning of Serbian literature. And with which the creation of Nemanja's cult, but also the cult of his family - the holy lineage of Nemanjić. Even before Nemanja, Serbs represented a political factor, sreated state unions that had their own cultural basis, legendary and historical traditions, but the real historical life of the Serbian people began with Stefan Nemanja. Sain Sava knew how important the close relationship between the church ant the state is for the future of the Serbian people, he was convinced that the mission of the church requires the support of the state and that the state, if it wants to be strong and stable, needs the support of the church. But it is also tempting to determinate the scope of work for each of them, because he also knew how dangerous it is if they start falling into each other's jurisdiction. The strenght and solidity of Sava's church was showen even after the collapse of the Serbian state, when it lived in foreign countries, because it became the property of the Serbian people with whom it shared its destiny - the church was the people, the people were the curch. These are the reasons for which it can rightly be said that, in addition to being the founder of the Serbian Church, which is the orginator of Serbian culture. Sain Sava is also the founder of the Serbian nation.